Periodization in college soccer. - Favero, T.; White, J. (Strength and Conditioning Journal, 2018)
Periodization optimizes training responses to improve performance. College soccer presents a unique challenge to periodized approaches because of a short preseason and condensed match schedule. Academic challenges of class time and intensive examination schedules impact athlete's sleep and interfere with full recovery often leaving athletes fatigued and tired during and at the end of the season. This article outlines a model system to organize periodized training over an entire year, including summer training, preseason, and the competitive collegiate season. Practical suggestions are offered to address academic and seasonal challenges while preventing injury, avoiding burnout, and late season performance declines.